Astronomical Review of the Pandita Board (Wong-Wong and Tike Lime) in Determining Good Days in Banyu Urip Village - Namira, Namira Marizkia Milinia; Eva Puspitasari (Universitas Islam Negeri Mataram, 2025)
The Pandita board is an ancestral heritage that has functions such as determining a good time for traveling, farming, or performing rituals. The Sasak community knows this board as Warige and is an interesting topic to discuss because the calculation results are quite accurate with modern astronomical calculations, where the calculation system refers to the movement of the Moon. This research aims to understand the system of determining good days using the Pandita Board (Wong-wong and Tike Lime), and analyze it based on the phases of the Moon. This research is field research with a qualitative approach. The data collection methods used are direct observation, unstructured interviews, and documentation using qualitative descriptive analysis methods. The results of this study are the system of determining good days using Papan Pandita seen from 3 concepts, namely, referring to the Rowot Sasak calendar which is the same as the urfi lunar calendar which has a month number of 29 or 30 days, calculating days, dates, and human characters using wong-wong and calculating time or hours using tike lime. Meanwhile, the determination of good days based on Papan Pandita is influenced by astronomical observations of the phases of the Moon. The phases of the Moon influence the determination of dates that are considered good or bad (Kalen Bulan). Kalen Bulan refers to certain phenomena such as eclipses, planetary conjunctions or positions of the Moon that are considered unfavorable.